RSMA Inspired User Cooperation in Hybrid VLC/RF Networks for Coverage Extension - Rallis, Konstantinos G.; Papanikolaou, Vasilis K.; Tegos, Sotiris A.; Dowhuszko, Alexis A.; Diamantoulakis, Panagiotis D.; Khalighi, Mohammad Ali; Karagiannidis, George K. (IEEE Wireless Communications and Networking Conference, WCNC, 2023)
In this paper, we propose and evaluate a hybrid visible light communication (VLC)/radio-frequency (RF) network architecture, where a VLC access point serves two user equipments (UEs), which also act as RF relays in order to extend the network's coverage to a third UE outside the VLC cell. The proposed protocol is inspired by uplink rate-splitting multiple access to efficiently route the messages to the UEs. In more detail, the proposed protocol utilizes the nuances of the specific network architecture to efficiently utilize the wireless resource blocks for both coverage and throughput. The protocol is then optimized by maximizing the minimum achievable rate. Simulation results show that the proposed method achieves superior results compared with a more conventional benchmark scheme, that is also optimized under the same constraints.
Created from Fastlane, Scopus look-up
Keywords: coverage extension; hybrid VLC/RF; max-min rate; resource allocation; Visible light communications